2022
DOI: 10.1111/and.14417
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol benefits on sperm DNA, chromatin structure and reproductive outcomes of varicocelized rats

Abstract: In varicocele, the main cause of sperm DNA damage is oxidative stress (OS).Resveratrol, a polyphenol with antioxidant properties, can protect cells from injuries caused by OS. We investigated the benefits of resveratrol against reproductive damage caused by experimental varicocele induced from peripuberty. Eighty peripubertal male rats were distributed into 4 groups: sham-control (S), varicocele (V), resveratrol (R) and varicocele treated with resveratrol (VR). Varicocele was induced through the partial ligatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Nevertheless, studies report an ipsilateral effect and a contralateral effect of the varicocele ( 19 ), leading to damage to the development of spermatogenesis, and secretory function of the Sertoli and Leydig cells on contralateral testis ( 20 ). Furthermore, ipsilateral and contralateral damage have been observed in sperm function parameters such as nuclear DNA integrity, mitochondrial activity, and acrosome integrity ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies report an ipsilateral effect and a contralateral effect of the varicocele ( 19 ), leading to damage to the development of spermatogenesis, and secretory function of the Sertoli and Leydig cells on contralateral testis ( 20 ). Furthermore, ipsilateral and contralateral damage have been observed in sperm function parameters such as nuclear DNA integrity, mitochondrial activity, and acrosome integrity ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…This in vitro evidence is corroborated by in vivo preclinical studies on rat models, highlighting the promising use of Resveratrol as a nutraceutical substance adjuvant to mitigate subfertility in varicocele [8,21,23]. As an example, Mendes et al demonstrated that Resveratrol partially reduces testicular apoptosis and reverses alterations in the sperm motility and promotes mitochondrial activity and DNA integrity [23], as well as improves the oxidative status and sperm vitality [21].…”
Section: Introductionmentioning
confidence: 91%
“…From a mechanistic point of view, these actions depend on different pathways; among them, Resveratrol is involved in the activation of antioxidant enzymes, such as catalase and superoxide dismutase, having a crucial role in the lipid damage of human spermatozoa [19]. Furthermore, Resveratrol shows an anti-inflammatory activity by the inhibition of COX2 and NF-KB [20] and protects cells from DNA damage and apoptosis by modulating antiand proapoptotic mediators, leading to an increase in sperm vitality, sperm DNA integrity, and an improvement in oxidative stress [21].…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes of different substances on the biochemical and morphological damages induced in testes by experimental varicocele were studied in the last years [7,[9][10][11][12][13][14][15]. In particular, the effects of lycopene and selenium (Se) were evaluated.…”
Section: Introductionmentioning
confidence: 99%